Pentahelix Model in the Development of Islamic Social Finance at Amil Zakat Institutions - Tun Rustam; Nuryanti; Haniah Lubis (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
This research aims to offer the concept of pentahelix in the management and development of modern Islamic social finance. This research is a qualitative research with a library study approach that seeks to explore and develop the concept of pentahelix that has not been applied to the management and development of Islamic-based social finance activities. The results of this discussion found a new concept related to the pentahelix concept in the management and development of Islamic social finance. What can be done is starting from the activeness of academics, business people, government, communities and the media. The five elements have an interrelated relationship and support each other in the concept of developing Islamic social finance. Academics play a role through education, service and research tasks that will prepare and equip knowledge to human resources who have managerial skills and mastery of the knowledge needed in the management of Islamic social institutions. The government also has a role in the development of Islamic social finance in the form of support by publishing the Sharia Economic Master Plan by the National Development Planning Agency (BAPENAS). These activities require community support, and the role of mass media is needed in order to provide information or education. The effectiveness of using mass media is considered to have more continuity and durability of information and accuracy in reporting.